Relevant clinical factors in the diagnosis of a posterior bite collapse. a systematic review 2021. - Balarezo Razzeto, José Antonio (2022)
The present research arises from a concern regarding the lack of consensus on the concept of posterior bite collapse on which there is currently very little literature. The Objective was identify the relevant clinical factors in the diagnosis of a posterior bite collapse. Is a systematic review based on reports and case series. Was considered as dimensions: dental occlusion, muscle tissue, temporomandibular joint, periodontal tissue and radiographic examination. Of 82 initially selected articles, the review was carried out with 6 articles. The information was ordered describing each one of them, being the publications between 1987 and 2020. We can Conclude that Relevant clinical factors for the correct diagnosis of a posterior bite collapse were identified according to the study dimensions: loss of teeth, alteration of the vertical dimension, periodontitis, deviation in the opening and closing of the TMJ, and bone resorption, as the most predominant according to the diagnostic dimensions.